2005
DOI: 10.1002/j.2161-1912.2005.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Individualism and Collectivism: What Do They Have to Do With Counseling?

Abstract: The author defines individualism and collectivism before examining how they are integral parts of the counseling process for clients and counselors. Although individualism has been assumed to be the norm for the counseling culture in the United States, recent work notes the influence of collectivism on professionals and clients in the counseling system. El autor define el individualismo y el colectivismo antes de examinar cómo ellos son partes esenciales del proceso que aconseja para clientes y consejeros. Aun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…In cultures where collectivist values are emphasized, relationships are rather stable and they are based on close in-groups (McCarthy 2005). In Turkey, counseling-type assistance often seems to take place through informal methods, such as support from family, and even through utilization of indigenous helping, which is also considered a significant part of help-seeking in Turkey (Öngel and Smith 1999).…”
mentioning
confidence: 99%
“…In cultures where collectivist values are emphasized, relationships are rather stable and they are based on close in-groups (McCarthy 2005). In Turkey, counseling-type assistance often seems to take place through informal methods, such as support from family, and even through utilization of indigenous helping, which is also considered a significant part of help-seeking in Turkey (Öngel and Smith 1999).…”
mentioning
confidence: 99%
“…This would minimize the justification of abnormality due to misunderstandings about unusual symptoms or to generalizing the idea of having mental health problems as being the same as some common illnesses (i.e., if someone catches a cold, they have fever and sore throat, or that someone with depression has moods that might swing from extremely subdued to manic). In addition, because religion is crucial to Iranians (McCarthy, 2005), they prefer to ask for help from religious people rather than psychological professionals (counselors). Thus the best way is to equip religious people with a vanguard of knowledge on mental health and advocate them to share the concept of mental health within their social network, preferably with those having the same religious background.…”
Section: Discussionmentioning
confidence: 99%
“…Diala et al (2000) also reported that people who are uncomfortable talking about personal issues with professionals in mental health care are five times less likely to seek assistance. Quite critically, people in collectivistic societies disclose to their family and friends, whom they perceive as trustworthy, but choose to not disclose to counselors (McCarthy, 2005). Therefore, people who are comfortable in disclosing their distress to family and friends are less likely to seek counseling.…”
Section: Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…Individualistic cultures as a whole are more likely to value autonomy and an individual perspective. In terms of collectivistic cultures, however, society is more influential in people's lives, and people identify themselves through their relationships with people around them (McCarthy, 2005). While an individualistic approach appears to be predominant in Westernized countries (e.g.…”
Section: Discussionmentioning
confidence: 99%